When do export subsidies have a redistributional role? - Holloway, G.J. (Wiley, 2002)
If an export subsidy is efficient,that is, has a surplus transfer role, then there exists an implicit function relating the optimal level of the subsidy to the income target in the agricultural sector. If an export subsidy to the income target in the agricultural sector. If an export subsidy is inefficient no such function exists. We show that dependence exists in large-export equilibrium, not in small-export equilibrium and show that these results remain robust to concerns about domestic tax distortions. The failure of previous work to produce this result stems from its neglect of the income constraint on producer surplus in the programming problem transferring surplus from consumers and tax payers to farmers.